Trap level analysis of Ce 3+ and Sm 3+ in Li 6 Y(BO 3 ) 3 - D. Joseph Daniel (2019)
© 2019 Elsevier Ltd and Techna Group S.r.l. The polycrystalline compounds of Li 6 Y(BO 3 ) 3 : Ce 3+ and Sm 3+ co-doped polycrystalline samples were prepared by using standard solid state reaction method. The energy levels of the doped lanthanide ions (Ce 3+ and Sm 3+ ) in the borate host materials were investigated by Thermoluminescence (TL) glow peak analysis. The co-doped samples, exhibits the TL peak at higher temperature region around 511 K whereas the Ce 3+ individually doped sample has peak around 433 K. The X-ray excited emission spectra were carried out for all the prepared samples and found the characteristic emission bands. The trap depths (E) were calculated by using several standard methods, namely peak shape method or chen's (PS), variable heating rate (VHR), initial rise (IR) and computerized glow curve deconvolution (CGCD). The mean activation energy of the co-doped samples found to be 1.21 (0.07±) eV and the frequency factor around 1.38 × 10 11 Sec −1 . The calculated trap depths and the predicted energy level values were compared and found in good agreement. This primarily results suggest that the energy level scheme can help in the development of new TL materials suitable in dosimetry.